GROWTH OF AXILLARY SHOOTS OF Alstonia scholaris (L.)R. Br. ON DIFFERENT HEIGHT OF HEDGING AND DOSAGES OF NPK FERTILIZER - Mashudi Mashudi; Hamdan Adma Adinugraha; Dedi Setiadi; Anita F Ariani (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
The aim of this experiment was to investigate the effect of hedging treatment and NPK fertilizer application on shoots production of Alstonia scholaris (L)R.Br. at nursery stage. The experiment was arranged in completely randomized design with two factors. The first factor was the height of hedging, consisted of 3 levels : 20 cm, 30 cm and 40 cm above the ground. The second factor was NPK fertilizer application, consisted of 4 levels : control (0g), 2 g, 4 g and 6 g. The result showed that the height of hedging, dosage of NPK fertilized and their interaction gave significant effect on the new shoots length. The highest shoot length by height of hedging treatment was 23.19 cm (T1) and the treatment of NPK fertilizer dosage was 23.18 cm (P4). The highest shoot length by interaction treatment was 26.87cm (P4T2). The treatment which showed the best average value of all characters was P1T1, as follows: number of shoots was 3,75, shoots length was 26,69 cm and number of leaves were 39.